2006
DOI: 10.1021/om060736q
|View full text |Cite
|
Sign up to set email alerts
|

[1]Ferrocenophanes, [1]Chromarenophanes, and [1]Vanadarenophanes with Aluminium and Gallium in Bridging Positions

Abstract: Aluminum- and gallium-bridged [1]ferrocenophanes (4a, 4b), [1]chromarenophanes (5a, 5b), and [1]vanadarenophanes (6a, 6b) were synthesized from the respective dilithiated sandwich compounds with element dichlorides (Me2Ntsi)ECl2 [E = Al, Ga; Me2Ntsi = C(SiMe3)2(SiMe2NMe2)] in moderate to high isolated yields (54−97%). The new intramolecularly stabilized aluminum compound (Me2NCH2tsi)AlCl2 (2a) was synthesized, but was proven to be unreactive with respect to [Fe(LiC5H4)2]·2/3TMEDA. The diamagnetic species 2a, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
1
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 41 publications
8
53
1
1
Order By: Relevance
“…Again, the carbonmetal distances to the seven-membered ring (2.200(5)-2.250(4) ) are significantly shorter than those to the fivemembered ring (2.298(2)-2.302(4) ). As already indicated by 13 C NMR data, both ring ligands adopt an almost coplanar arrangement, which is reflected by the angles a = 0.78 and d = 179.58, and the bridging C and Si atoms exhibit a distorted tetrahedral geometry. The most important geometrical parameters of compounds 4-6 and 8-11 are summarized in Table 2.…”
Section: Metalloarenophanes Such As [Ma C H T U N G T R E N N U N G (supporting
confidence: 59%
See 2 more Smart Citations
“…Again, the carbonmetal distances to the seven-membered ring (2.200(5)-2.250(4) ) are significantly shorter than those to the fivemembered ring (2.298(2)-2.302(4) ). As already indicated by 13 C NMR data, both ring ligands adopt an almost coplanar arrangement, which is reflected by the angles a = 0.78 and d = 179.58, and the bridging C and Si atoms exhibit a distorted tetrahedral geometry. The most important geometrical parameters of compounds 4-6 and 8-11 are summarized in Table 2.…”
Section: Metalloarenophanes Such As [Ma C H T U N G T R E N N U N G (supporting
confidence: 59%
“…As expected, the incorporation of a triatomic bridge in [Ti(h 5 [43] and show two signals for the C 5 H 4 protons at d = 5.02 and 5.10 ppm and one multiplet for the C 7 H 6 moiety at d = 5.53 ppm. In addition, deshielded resonances of the ipso-carbon atoms are observed in the 13 C NMR spectrum (C 5 H 4 : 110.3 ppm; C 7 H 6 : 94.9 ppm), which is consistent with the unstrained character of 11.…”
Section: Metalloarenophanes Such As [Ma C H T U N G T R E N N U N G (supporting
confidence: 54%
See 1 more Smart Citation
“…Surprisingly little information is available on ferrocenylaluminum compounds. Recently, it has been shown that the reactions of 1,1 0 -dilithiated ferrocene fcLi 2 with organoaluminum dihalides afford ferrocenophanes with aluminum in the bridge, stabilised by intramolecular coordination [5,6], 1,1 0 -disubstituted ferrocene [7] or rather novel types of ferrocenylaluminum compounds [6b,8]. Ferrocenylmercury chloride reacts with trialkylalanes to give mixed dimers 2 [9].…”
mentioning
confidence: 99%
“…A related galla[1]ferrocenophane was published by Lund et al (2006). For related literature, see: Bellas & Rehahn (2007) ;Foucher et al (1992); Herbert et al (2007); Lund et al (2007); Osborne & Whiteley (1975); Schachner et al (2005aSchachner et al ( , 2007.…”
Section: Related Literaturementioning
confidence: 99%